PERBANDINGAN METODE EKSTRAKSI DAN VARIASI PELARUT TERHADAP RENDEMEN DAN AKTIVITAS ANTIOKSIDAN EKSTRAK KUBIS UNGU (Brassica oleracea L. var. capitata f. rubra) - Rima Yulia Senja; Elisa Issusilaningtyas; Akhmad Kharis Nugroho; Erna Prawita Setyowati (Faculty of Pharmacy, Universitas Gadjah Mada, 2014)
Red Cabbage (Brassica oleracea L. Var. Capitata f. rubra) has a high anthocyanin content therefore it can be potential as a natural antioxidant. In this research, the antioxidant activity of the red cabbage extract was evaluated quantitatively with a spectroscopy method using DPPH reagent to obtain the value of IC50 . This research was divided into 2 stages. First, the influence of solvent variant to the extract yield of red cabbage powder and the maximum wavelength (λ) using a maceration protocol. The kind of solvent (70%, 80%, 95%, and 96% of ethanol) with addition 3% of citric acid. Second, the influence of extraction methods in neutral condition to the antioxidant activity. The results show the red cabbage powder maceration with 96% ethanol solvent (acid condition) exhibits the highest yield. The fresh red cabbage soxhletation with 96% ethanol (neutral condition) exhibits 288,5 nm maximum wavelength (λ) and 168,78 mg/mL of IC50 value.